The Moderating Role of Age: The Influence of Service Quality and Word of Mouth on Customer Loyalty with Trust as an Intervening Variable in the Banking Industry - Qomariah, Nurul; Andhika, Stanly Reza; Herlambang, Toni; Martini, Ni Nyoman Putu; Sari, Mutiara Dwi (Universitas Brawijaya, Indonesia, 2025)
The increase in customers who experience delays and bad debts indicates a challenge in maintaining the quality of customer relationships and loyalty, despite the bank's success in attracting new customers. Although the number of customers continues to increase, the rise in arrears and bad debts suggests potential issues in customer relationship management. Therefore, the purpose of this study is to determine and analyze the effect of service quality and word of mouth on customer loyalty at the BRI Jember Branch, with customer trust serving as an intervening variable. This study method employs a descriptive quantitative approach, utilizing Structural Equation Modeling (SEM) data analysis techniques processed with the WarpPLS 8.0 Application. The population in this study was 531,266 customers. The study comprised 400 research samples, selected using a purposive sampling technique. The results showed that service quality and word of mouth had a significant effect on customer trust at the BRI Jember Branch. Service quality, word of mouth, and customer trust have a significant impact on customer loyalty at the BRI Jember Branch. Indirectly, service quality and word of mouth have a significant effect on customer loyalty through customer trust as an intervening variable at the BRI Jember Branch. Regarding the moderation variable, the age variable moderates the influence of word of mouth on loyalty. On the other hand, the age variable does not strengthen the influence of service quality on loyalty. This finding has practical implications for banking institutions to continue improving service quality and enhancing word of mouth, as it has been proven to increase customer trust and loyalty.